ASSOCIATION OF SIPPING ICE THERAPY WITH THIRST AND XEROSTOMIA AMONG ADULT HEMODIALYSIS PATIENTS: AN EXPLORATORY AND A QUASI-EXPERIMENTAL PRETEST–POSTTEST STUDY - Moh Faris K.L. Harahap; Asep Kuswandi; Dewi Aryanti; Yanti Cahyati (International Archives of Medical Sciences and Public Health, 2026)
Thirst and xerostomia are distressing symptoms in hemodialysis (HD) patients. This study examined the association between sipping ice therapy and these symptoms among adult HD patients. A quasi-experimental pretest–posttest study with a non-equivalent control group was conducted at Banjar Hospital, Indonesia. Forty adults were allocated via purposive sampling to an intervention (n = 20) or control group (n = 20). The intervention group received sipping ice therapy (5 ?mL ice cubes, up to eight daily) for six consecutive days at home, while controls received routine care. Symptoms were measured using the Dialysis Thirst Inventory and Summate Xerostomia Inventory. The intervention group demonstrated significant reductions in median thirst and xerostomia categories from severe to mild (both p < 0.001), whereas no significant changes occurred in controls. Posttest between group comparisons strongly favored the intervention for reducing thirst (p < 0.001,r = 0.91) and xerostomia (p < 0.001,r = 0.88). Sipping ice therapy substantially reduces thirst and xerostomia in adult HD patients, serving as a feasible, non-pharmacological adjunct in nephrology nursing care. Future multi-center randomized trials are warranted.